Transition Metal Carbides and Nitrides as Electrode Materials for Low Temperature Fuel Cells - Jae Sung Lee; Dong Jin Ham (Energies, 2009)
Transition metal carbides (TMCs) and transition metal nitrides (TMNs) have attracted attention as promising electrocatalysts that could replace noble metals of high price and limited supply. Relative to parent metals, TMC and TMN behave like noble metals for electrochemical reactions such as oxidation of hydrogen, CO and alcohols, and reduction of oxygen. When TMC and TMN are combined with other metals, the electrocatalytic synergy is often observed in electrochemical reactions. Thus, combinations with a minute amount of Pt or even non-Pt metals give performance comparable to heavily loaded Pt-based electrocatalysts for low temperature fuel cells. It appears that TMC based electrocatalysts are more active as anode catalysts for oxidation of fuels, whereas TMN based catalysts are more active for cathode catalysts for oxygen reduction and more stable.